Coriandrum sativum mediated synthesis of silver nanoparticles and evaluation of their biological characteristics. (23rd May 2018) - Senthilkumar, N; Aravindhan, V; Ruckmani, K; Potheher, I Vetha
Abstract: Silver (Ag) nanoparticles (NPs) were prepared by percolated green synthesis method using Coriandrum sativum leaf, root, seed and stem extracts and reported its antibacterial activity. The synthesized Ag NPs were confirmed by UV–visible Spectroscopy, Powder x-ray Diffraction (PXRD), Fourier Transform Infra Red (FT-IR) Spectroscopy analyzes. The Maximum absorbance observed around 400–450 nm reveal the characteristic absorbance of Ag NPs. The Dynamic Light Scattering (DLS) analysis shows the stability of synthesized NPs with average size varying from 35 to 53 nm and also zeta potential stability varying from −20 to −30 mV. The cubic structure, crystalline nature and purity of the material was confirmed by powder x-ray diffraction studies. FT-IR spectrum shows the presence of various functional groups in the resultant material. The Field Emission Scanning Electron Microscopy (FESEM) image shows the surface morphology of the synthesized NPs and the Energy Dispersive x-ray Analysis (EDAX) confirms the presence of silver metal ions. The Coriandrum sativum aqueous extract exhibited excellent antimicrobial activity against Klebsiella pneumoniae (Gram -ve) bacteria. Numerous studies have been made previously in our field of study but optimization has not been carried out by both extract (different parts like leaf, root, seed and stem) and without addition of any external source such as chemicals, heat etc.